COMPARISON OF THE EFFECT OF PTEROCARPUS MARSUPIUM WITH PIOGLITAZONE IN DEXAMETHASONE-INDUCED INSULIN RESISTANCE - Narendar, Koyagura; Nagendra Nayak, I M; Jamadar, M G; M Patil, Ashok; Anand, Sanjit (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study was undertaken to evaluate the preventive effect of heartwood of P. marsupium in dexamethasone-induced hyperinsulinemia and hyperglycemia and compare it with that of pioglitazone. Methods: Male albino wistar rats were divided into five groups (n=6). Plain control group received gum acacia (2%) orally from d 1 to d 12. Dexa control group received gum acacia (2%) orally for d 1 to d 12 and Dexa (8 mg/kg) intraperitoneal (i.p.) from d 7 to d 12, during the study period. Two test groups received ethanolic extract of Pterocarpus marsupium heartwood (PME) (1 and 2 g/kg/) per oral (PO), and standard control group received pioglitazone (60 mg/kg/PO) from d 1 to d 12. During the 12-d study period, the two test groups and standard control group received Dexa (8 mg/kg/i.p.) from d 7 to d 12. On last day of the study, the blood samples were collected by retro-orbital sinus punctureand used for estimation of serum insulin and glucose levels. Homeostatic Model Assessment (HOMA) method was employed to calculate the degree of insulin resistance(IR). Results were analyzed by using one-way analysis of variance followed by Scheffe's multiple comparison test (p<0.05). Results: Treatment with ethanolic extract of P. marsupium and pioglitazone significantly (p<0.05) reduced the elevated insulin and glucose levels as well as HOMA-IR and HOMA-IS values in dexa treated animals. Conclusion: Ethanolic extract of P. marsupium heartwood effectively countered dexamethasone-induced hyperinsulinemia and hyperglycemia. Insulin-sensitizing activity of P. marsupium heartwood was found to be more effective than pioglitazone. Keywords: Pterocarpus marsupium, Insulin resistance, Hyperinsulinemia, Hyperglycemia.